Effect of Glycerin Addition as an Extender on the Properties of Mahogany Tannin-Based Adhesive and Particleboard Performance - Evul Ardiansyah; Andi Sri Rahayu Diza Lestari; Sahriyanti Saad; Musrizal Muin; Astuti; Heru Arisandi (JURNAL AGRIMENT, 2026)
The adhesive industry still relies on petroleum-based synthetic adhesives, necessitating the development of more sustainable alternatives. This study explored the use of tannin extracted from mahogany (Acacia sp.) bark as the basis for a Tannin Resorcinol Formaldehyde (TRF) adhesive a bio-based formulation that has received limited attention as a binder for particleboard applications. Glycerin was incorporated as an extender at concentrations of 5%, 10%, and 15% to improve bonding performance. Adhesive properties were evaluated according to SNI 06-0121-1987, while physical and mechanical properties of particleboards (21 cm × 21 cm × 1 cm) were tested according to SNI 03-2105-2006. Adhesive viscosity ranged from 4.42 to 4.46 cP, which did not meet SNI requirements. Among all treatments, the 15% glycerin concentration yielded the best overall performance, producing the highest density (0,83 g/cm³), MOR (85,79 kgf/cm²), and internal bond (2,24 kgf/cm²), all of which met SNI 03-2105-2006. However, thickness swelling (14.66–16.29%) and MOE values across all treatments failed to meet the standard, indicating that glycerin alone is insufficient to ensure dimensional stability and board stiffness. These findings suggest that while 15% glycerin is the optimal concentration in this formulation, further optimization (such as increasing tannin solid content or combining glycerin with hydrophobic extenders) is needed to produce particleboard that comprehensively meets SNI requirements.